Tafsir dan New Media: Studi Penafsiran Ustadz Zulkifli Muhammad Ali di Youtube - Yassinta Ananda; Novizal Wendry; Lukmanul Hakim (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2022)
At the time of the Prophet Muhammad, the Companions, and the Tabi'in, the interpretation of the Qur'an was carried out directly orally and listened to by Muslims. Along with the times, there have been commentators who are active in interpreting the Qur'an as evidenced by the emergence of popular classical commentary books such as the interpretation of Ibn Kathir and others. In today's era where the development of science and technology is increasingly advanced, various forms of interpretation appear on various social media such as Youtube and Facebook. One of them is Ustadz Zulkifli Muhammad Ali through a Youtube account called UZMA Media TV Channel. This study aims to determine the method of Ustadz Zulkifli in interpreting the verses of the Qur'an as a proposition in lecturing starting from January 2, 2020-January 3, 2021. This study uses a qualitative method with a literature study approach where the data is obtained from the results of a collection of UZMA video lectures and books, journals, articles, and theses. The results of this study are in the form of a classification of the themes of UZMA lectures in the past year, including around the end of time, life guidelines (practice and worship), ethics, and muamalah, the Covid-19 outbreak. The maudhu'i method of interpretation has not met several criteria and has a systematic interpretation. There are two lecture responses, namely rejectionist and receptionist.